Keratinocyte proinflammatory responses to adherent and nonadherent group A streptococci. - Wang, B (1997)
The gram-positive bacterium Streptococcus pyogenes (group A streptococcus) is the causative agent of a wide variety of suppurative infections of cutaneous tissues. Previous analyses have demonstrated that the M protein of S. pyogenes is an adhesin that directs the attachment of the streptococcus to keratinocytes in the skin. In this study, we have examined keratinocyte function in response to S. pyogenes and found that adherent versus nonadherent streptococci promote distinct patterns of expression of several proinflammatory molecules and keratinocyte cell fate. When analyzed by a quantitative reverse transcriptase PCR method, infection of cultured HaCaT keratinocytes with adherent, but not nonadherent, streptococci resulted in increased expression of mRNA for the cytokines interleukin-1alpha (IL-1alpha), IL-1beta, and IL-8 but neither infection induced expression of tumor necrosis factor alpha. In contrast, both adherent and nonadherent S. pyogenes induced expression of IL-6 and each promoted synthesis and release of prostaglandin E2 (PGE2). However, considerably greater levels of IL-6 expression were stimulated by adherent streptococci relative to nonadherent streptococci and the kinetics of PGE2 release in response to nonadherent streptococci was delayed compared to the response to adherent streptococci. Staining with the fluorescent probe ethidium homodimer-1 revealed that keratinocyte membranes were rapidly damaged upon infection with adherent streptococci but were not damaged by nonadherent streptococci. Finally, treatments which inhibited streptococcal metabolism completely blocked the ability of adherent streptococci to elicit responses. These data suggest that expression of an adhesin is a strategy used by S. pyogenes to modulate keratinocyte responses during infection of the skin and implicate additional streptococcal products in these signaling interactions.